PIWIL1 Drives Chemoresistance in Multiple Myeloma by Modulating Mitophagy and the Myeloma Stem Cell Population - Wang, Yajun; Yao, Lan; Teng, Yao; Yin, Hua; Wu, Qiuling (Frontiers in Oncology, 2022)
As an important member of the Argonaute protein family, PIWI-like protein 1 (PIWIL1) plays a key role in tumor cell viability. However, the exact function of PIWIL1 in multiple myeloma (MM) and the underlying mechanism remain unclear. Here, we revealed that PIWIL1 was highly expressed in myeloma cell lines and newly diagnosed MM patients, and that its expression was notably higher in refractory/relapsed MM patients. PIWIL1 promoted the proliferation of MM cells and conferred resistance to chemotherapeutic agents both in vitro and in vivo. More importantly, PIWIL1 enhanced the formation of autophagosomes, especially mitophagosomes, by disrupting mitochondrial calcium signaling and modulating mitophagy-related canonical PINK1/Parkin pathway protein components. Mitophagy/autophagy inhibitors overcome PIWIL1-induced chemoresistance. In addition, PIWIL1 overexpression increased the proportion of side population (SP) cells and upregulated the expression of the stem cell-associated genes Nanog, OCT4, and SOX2, while its inhibition resulted in opposite effects. Taken together, our findings demonstrated that PIWIL1 induced drug resistance by activating mitophagy and regulating the MM stem cell population. PIWIL1 depletion significantly overcame drug resistance and could be used as a novel therapeutic target for reversing resistance in MM patients.